Intermittent left bundle branch block - reversal to normal conduction during general anesthesia - Silva,Ana Maria Oliveira Correia da (2017)
Abstract Background and objectives: Transient changes in intraoperative cardiac conduction are uncommon. Rare cases of the development or remission of complete left bundle branch block under general and locoregional anesthesia associated with myocardial ischemia, hypertension, tachycardia, and drugs have been reported. Complete left bundle branch block is an important clinical manifestation in some chronic hypertensive patients, which may also be a sign of coronary artery disease, aortic valve disease, or underlying cardiomyopathy. Although usually permanent, it can occur intermittently depending on heart rate (when heart rate exceeds a certain critical value). Case report: This is a case of complete left bundle branch block recorded in the preoperative period of urgent surgery that reverted to normal intraoperative conduction under general anesthesia after a decrease in heart rate. It resurfaced, intermittently and in a heart-rate-dependent manner, in the early postoperative period, eventually reverting to normal conduction in a sustained manner during semi-intensive unit monitoring. The test to identify markers of cardiac muscle necrosis was negative. Pain due to the emergency surgical condition and in the early postoperative period may have been the cause of the increase in heart rate up to the critical value, causing blockage. Conclusions: Although the development or remission of this blockade under anesthesia is uncommon, the anesthesiologist should be alert to the possibility of its occurrence. It may be benign; however, the correct diagnosis is very important. The electrocardiographic manifestations may mask or be confused with myocardial ischemia, factors that are especially important in a patient under general anesthesia unable to report the characteristic symptoms of ischemia.